2022
DOI: 10.3389/fonc.2022.939819
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transplant gene profiling characterization by next-generation DNA sequencing might predict relapse occurrence after hematopoietic stem cell transplantation in patients affected by AML

Abstract: BackgroundIn the last decade, many steps forward have been made in acute myeloid leukemia prognostic stratification, adding next-generation sequencing techniques to the conventional molecular assays. This resulted in the revision of the current risk classification and the introduction of new target therapies.Aims and methodsWe wanted to evaluate the prognostic impact of acute myeloid leukemia (AML) mutational pattern on relapse occurrence and survival after allogeneic stem cell transplantation. A specific next… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…An increasing number of genetic and epigenetic abnormalities have been shown to display the prognostic value in acute myeloid leukemia (AML); in this context, in a monocentric experience, ( 2 ) focused their attention on the prognostic impact of the mutational pattern of AML on relapse and survival after alloSCT. They found that FLT3, TP53, and WT1 mutations were predictive variables associated with a higher rate of relapse occurrence after transplant.…”
mentioning
confidence: 99%
“…An increasing number of genetic and epigenetic abnormalities have been shown to display the prognostic value in acute myeloid leukemia (AML); in this context, in a monocentric experience, ( 2 ) focused their attention on the prognostic impact of the mutational pattern of AML on relapse and survival after alloSCT. They found that FLT3, TP53, and WT1 mutations were predictive variables associated with a higher rate of relapse occurrence after transplant.…”
mentioning
confidence: 99%